The Hıstologıcal Evaluatıon Of The Effect Of Nance Applıance On The Palatal Mucosa - Yahya Tosun; Şükrü Özdamar; Şafak Tezcan; Serhat Yalçın; Mehmet Özgen (Galenos Yayinevi, 1992)
Nance appliance is a device utilized to reinforce the anchorage when combined with fixed appliances, exerting a permanent force on the palatal mucosa. In the study, the effects of Nance appliance on palatal mucosa was investigated histologically. After a period of 9 months, in 10 subjects, a parakeratosis and also an infiltration of mononuclear cells presenting a chronic tissue inflammation under the acrylic button.